Leuwikeris Agricultural Development In Supporting The Development Of Ecological Agriculture In Ciamis District - Dadi Dadi (Institute of Computer Science (IOCS), 2020)
One of the efforts to improve the country's economy through the development of agro-tourism in several areas is strategically functioned by the government to fulfill welfare among the wider community, especially in some areas that do have a variety of tourism potential based on natural resources that are still maintained until now. This research uses a case study method with a qualitative approach and data triangulation analysis, the results of the study explain that as one of the districts that has a variety of agro-tourism potential spread in various parts of the Ciamis Regency area, it is considered to have succeeded in increasing the potentials contained in natural resources. Accordingly, the development must be based on the development and welfare of the community, besides that Ciamis Regency is also busy with a mega project that is engaged in the use of land and nature, namely the construction of the Leuwikeris dam. able to function as the development of an agro-tourism system based on ecological agriculture that is more equitable and comprehensive, the agro-tourism system that emphasizes the agricultural sector through the Leuwikeris dam is expected to be able to synergize and greatly affect the welfare of the community. public interest nationally.